A interpretação em Paul Ricoeur: uma discussão para a reformulação da hermenêutica - Pieterzack, Cristiane (2009)
This research pretends to examine the prosposal for revision of the hermeneutic project develened by Paul Ricoeur fron the viewooint of the debate between the Hermeneutic of Tradition and the Critique of Ideologies prososed by Gadamer and Habermas. The study begins discussing origins of the concept of hermeneutics and its relation to the notione of interpretation and comprehension as they appear in the thought of Heidegger, heir of a tradition which comes from Scheleiermacher and Dilthey. The study continues showing how, after a linguistic tour of philosophy, there is a growing recognition that the access to objectives comes about through a sense of good judgement in the historical world. Gadamer, after restoring the concepts of tradition and authority, show convincingly the link between historicity and comprehension. Habermas adds that he perceives a need to maintain a critical edge to human thought so that the hermeneutics not lead to a kind of linguistic idealism, once the limits of language are set aside. Placing himself in the dialogue between the hermeneutic reasoning of Gadamer and the critical reasoning of Habermas. Paul Ricoeur presents the possibility of critical-hermeneutic rational thought, developing a theory of text. To the extent that the hermentutic is an interpretation that leads to written language, it comes to possess, in itself, indications that it not only belongs to a condition of historicity, but that it also offers a critique os ideologies. What permits this is the conception of text, a model of distancing that does not alienat, while remaining autonomous in relation to the author, the occurence of the original situation, the original recipient, and in relation to any other recipient.